2020
DOI: 10.3390/e22101187
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Rules: Molecular Dynamics Simulations of Model Oligomers for Thermoresponsive Polymers

Abstract: We attempted to attain atomic-scale insights into the mechanism of the heat-induced phase transition of two thermoresponsive polymers containing amide groups, poly(N-isopropylacrylamide) (PNIPAM) and poly(2-isopropyl-2-oxazoline) (PIPOZ), and we succeeded in reproducing the existence of lower critical solution temperature (LCST). The simulation data are in accord with experimental findings. We found out that the entropy has an important contribution to the thermodynamics of the phase separation transition. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In prior publications, we found that thermodynamic quantities, such as the enthalpy, may vary significantly between repeated simulations of the CGT. , Conclusively, we presumed the conformational diversity in both states to be of particular importance. Besides, we were convinced that the thermosensitive character of the CGT originates from an entropic effect. , Specifically, we assumed that a large variety of globular structures exist, whose properties show significant deviations in terms of thermodynamics and kinetics. However, as of now, distinguishing between conformational substates has been challenging due to the lack of suitable descriptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior publications, we found that thermodynamic quantities, such as the enthalpy, may vary significantly between repeated simulations of the CGT. , Conclusively, we presumed the conformational diversity in both states to be of particular importance. Besides, we were convinced that the thermosensitive character of the CGT originates from an entropic effect. , Specifically, we assumed that a large variety of globular structures exist, whose properties show significant deviations in terms of thermodynamics and kinetics. However, as of now, distinguishing between conformational substates has been challenging due to the lack of suitable descriptors.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, we were convinced that the thermosensitive character of the CGT originates from an entropic effect. 18 , 22 24 Specifically, we assumed that a large variety of globular structures exist, whose properties show significant deviations in terms of thermodynamics and kinetics. However, as of now, distinguishing between conformational substates has been challenging due to the lack of suitable descriptors.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic metal-chelating polymers are an important technology to neutralize and remove metal contaminants from solution. Several polymers have been synthesized and tested for metal sequestration applications, using isothermal titration calorimetry (ITC) to measure the binding thermodynamics of polymers to metal ions. While ITC enables the direct measurement of heat associated with metal ion binding in solution, it is a global technique that determines the total entropy and cannot separate the competing effects of coupled events (e.g., ion binding versus (de)solvation versus polymer conformation changes). , Computational approaches can enable greater insight into polymer-metal ion interactions by focusing on time and length scales that are inaccessible to ITC or other experimental techniques. , Atomistic simulations such as molecular dynamics (MD) are well-suited to the simulation of entropic effects, but the quantification of functional properties from MD is nontrivial. .25ex2ex F⃗ false( r⃗ , t false) = q E⃗ total false( r⃗ , t false) = q false( E⃗ water ( r⃗ , t ) + E⃗ polymer ( r⃗ , t ) + ... false) = q k E⃗ k false( r⃗ , t false) …”
Section: Introductionmentioning
confidence: 99%
“…bonds formed between the protein and ligand that results in suitable complex formation between the biomolecules [49,51]. It also provides supports for the small range of uctuations observed in RMSD plot.…”
Section: Discussionmentioning
confidence: 58%